2009
DOI: 10.21608/jpp.2009.116677
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Productivity of Giza 80 Cotton Cultivar as Affected by Foliar Feeding With Boron and Zinc.

Abstract: Two field experiments were carried out at Sids Agric. Res. Station, Beni-Suef Governorate, in 2007 and 2008 seasons. The experiment was conducted to evaluate the effect of foliar feeding with B and/or Zn on growth and productivity of the Egyptian cotton Giza 80 cultivar (G. barbadense L.,) to study response of growth, fruiting and yield. Besides the control treatment, two concentrations of both boron (85 and 170 ppm) and zinc (180 and 360 ppm) and their combinations were applied twice; at the start and peak of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…of open bolls / plant, boll weight, seed index as well as lint percentage due to the important role of B stimulating pollen germination and pollen tube growth resulting in successful fruit setting. These results are similar to those obtained by Niaz et al (2002) and El-Menshawy and El-sayed (2007) and Kassem et al (2009) indicated that spraying boron showed positive effects on cotton which significantly increased No. of open bolls/plant, boll weight and seed cotton yield/fed.…”
Section: Growth Characterssupporting
confidence: 91%
See 2 more Smart Citations
“…of open bolls / plant, boll weight, seed index as well as lint percentage due to the important role of B stimulating pollen germination and pollen tube growth resulting in successful fruit setting. These results are similar to those obtained by Niaz et al (2002) and El-Menshawy and El-sayed (2007) and Kassem et al (2009) indicated that spraying boron showed positive effects on cotton which significantly increased No. of open bolls/plant, boll weight and seed cotton yield/fed.…”
Section: Growth Characterssupporting
confidence: 91%
“…Similar results were obtained by Kassem and Alia (2003) and Schworz and Mendel (2006) who indicated that Mo. Is an essential element for higher plants and plays a vital role in many physiological and biochemical processes while, Kassem et al (2009), found that spraying boron showed positive effects on cotton which significantly increased plant height and number of fruiting branches per plant. were increased significantly by spraying Eth.…”
Section: Growth Characterssupporting
confidence: 86%
See 1 more Smart Citation
“…In this regard, B is essential for cell wall formation; it plays a vital role in the growth and development of new cells and regulates auxin production in plants (Hamoda 2012;Zoz et al 2016). Kassem et al (2009) and Karadmir & Karademir (2020) stated that spraying with B had positive effects on cotton, which significantly increased plant height, number of fruiting branches, number of opened bolls/plant, boll weight, and seed cotton yield (k/f). In contrast, the favorable effects of Ca in cotton yield components might be attributed to the important role in enhancing photosynthesis and maintaining turgor under drought stress conditions.…”
Section: Effects Of the Main Factors And Their Interactions On The Yi...mentioning
confidence: 99%
“…More et al (2018) revealed the positive effects of spraying with B on growth, fruit retention, and yield components of cotton. Kassem et al (2009), Hamoda (2012), and Karademir & Karadmir (2020) illustrated that foliar application of B gives the highest values in leaves content of N, P, K, Mg, B, Fe, Mn, and Zn and significantly increases the seed cotton yield compared to control. Mixed Ca-B is essential for pollen grain germination and pollen tube elongation by helping in successful fertilization or pollination and banning the abortion of flowers.…”
Section: Introductionmentioning
confidence: 99%